THE PERCEPTION OF LEARNING OF DISADVANTAGED GROUPS OF ADULTS - Mickūnaitė, Elena (Acta Paedagogica Vilnensia, 2008)
The paper presents research data about the conception of learning of unemployed disadvantaged groups of adults through their perception of learning value and its benefits. Ten focus group interviews were conducted to represent five different disadvantaged groups and to find out their perception of learning, authentically underpinned by their own understanding and social context. It comes out that the interviewees hold a positive attitude towards learning and perceive its value in a contemporary life, but they tend to project a learning possibility to other, younger, better-to-do individuals who hold a higher social status. The interviewees see the value of learning directly connected with employment and, therefore, they want practical training based courses to gain simple and competetive skills or learn crafts. Besides, they want to learn in a traditional way without taking advantage of independent or distance learning.
Keywords: lifelong learning; learning value; disadvantaged groups of adults; social inclusion